The role of prosocial tendencies in the relationships between gratitude, perceived social support, and psychological well-being among Chinese university students: a structural equation modeling approach - Man, Xu; Jing, Zhang (Frontiers in Psychology, 2025)
IntroductionThis study explores the relationships among gratitude, perceived social support, prosocial tendencies, and psychological well-being (PWB) in Chinese university students. Despite growing interest in these constructs, the mechanisms through which gratitude and social support influence PWB remain underexplored, particularly in collectivist cultural contexts where social harmony and interdependence are prioritized.MethodsData were collected from 703 Chinese university students using validated instruments measuring gratitude, perceived social support, prosocial tendencies, and psychological well-being. Structural equation modeling (SEM) was employed to test the direct and indirect effects of gratitude and social support on PWB, with prosocial tendencies modeled as a mediating higher-order factor. Multi-group SEM analysis was conducted to examine gender invariance.ResultsGratitude and perceived social support significantly predicted PWB, both directly and indirectly through prosocial tendencies. Gratitude had a strong positive effect on prosocial tendencies (β = 0.412, p < 0.001), which, in turn, significantly contributed to PWB (β = 0.465, p < 0.001). Similarly, perceived social support positively influenced prosocial tendencies (β = 0.375, p < 0.001) and PWB (β = 0.253, p < 0.05). Mediation analysis confirmed that prosocial tendencies partially mediated these relationships. Multi-group SEM analysis revealed structural invariance across gender.DiscussionThe findings underscore the cultural relevance of gratitude and social support within Chinese society, emphasizing the role of collectivist values in fostering PWB. Practical implications include implementing gratitude-focused interventions and enhancing peer support systems within university mental health programs to promote resilience and well-being among students.